Self - medication practices among medical and non - medical university students: the prevalence, knowledge and attitudes - Murahwa, Rumbidzai (My University, 2020)
The practice of self - medication has formed a momentous area within healthcare systems, and has increasingly become a common practice globally. There have been several reports addressing the prevalence of self - medication practices among university students in other countries, but none from South Africa. The main aim of this study was to determine the prevalence, knowledge and attitudes of self - medication practices among medical and non - medical university students enrolled at the University of the Witwatersra nd, Johannesburg. Subjects and methods In this study, undergraduate pharmacy students were designated as the “medical” students, while undergraduate psychology students constituted the “non - medical” students. A pre - validated and self - administered question naire was distributed to medical and non - medical university students in a cross - sectional design. Data was analysed using the R statistical software (version R 3.6.1) , and the descriptive results were presented as counts and percentages. These were illustr ated using pie charts, bar charts and tables. Multinomial logistic regression models were used to investigate the four variables, sex, self - care orientation, medication knowledge and type of school (medical/non - medical) for possible correlation with self - m edication practices. Results Self - medication practices were reported by 77.8% of the respondents (n= 473 ). The prevalence rates reported for the medical and non - medical student groups were 84.9% and 73.5%, respectively. The majority of females were self - medicating than males, 79.4% and 20.1%. A total of 168 (45.7%) respondents reported a high level self - care orientation, whilst 148 (40.2%) respondents reported “good” medication knowledge. Multinomial logistic regression models indicated that sex, medication knowledge and type of school attended where insignificant predictors of self - medication (p - value>0.05), whereas self - care orientation was a significant predictor (p - value<0.05). An individual’s level of self - care orien tation was significantly associated with the selection of a therapeutic class of medicine. For both groups of the study respondents, t he most commonly reported reasons for self - medication were “ Health problem is not serious”, “Quick relief”, “Previous exp erience with same illness” and “Personal convenience” amounting to 66.6%, 64.4% , 63.3% and 51.6% respectively. The most popular health conditions treated by self - medication for both groups of study respondents were headache (76.1%), colds, flu and sore thr oat (69.3%) and pain (63.6%). Analgesics (78.8%) were the most commonly reported class of medicine used in self - medication by all study respondents . There was no significant difference between the self - medication practices of medical and non - medical students (p - value = 0.83) Conclusions The practice of s elf - medication in the study was prevalent and common among both the medical and non - medical unive rsity students. There was, however, no significant difference in the practice of self - medication among the medical and non - medical students. Analgesics and anti - inflammatories were the most commonly used medicines for self - medication, and the frequency of use of these medicines could be minimised by raising student s ’ awareness and knowledge of the indications, contra - indications and side - effects of these medicines. The level of self - care orientation of an individual significantly influenced the choice of t herapeutic classes of medicines used in self - medication. A greater involvement of pharmacists in patient education regarding the practice of self - medication is needed . Student health groups in universities, with the help of pharmacists and physicians, coul d assist in promoting student awareness on rational medicine usage. Future research regarding the prevalence of self - medication at a national level or among other cohorts is recommended. It is imperative to pro vide extensive public education regarding rati onal medicine use, and to implement strategies and guidelines that promote the safe dispensing of medicines, which is the cornerstone for the appropriate and safe practice of self - medication. This study employed a cross - sectional design which provided insi ght into the cur rent self - medication practices, which might differ in other seasons. As a result, the study is unable to produce findings for long - term trends of self - medication practices of university students in South Africa. .
A dissertation submitted in fulfilment of the requirements for the degree of Master of Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2020